Meningkatkan Kemampuan Kosakata Anak Dengan Game Literasi Digital Melalui Aplikasi Wordwall - Salsabila, Chairunisa; Nurjannah, Eka; Elvira, Elvira; Maysaroh, Siti; Ulida, Ulida; Utami, Winda Sherly (Innovative: Journal Of Social Science Research, 2025)
Vocabulary skills are a fundamental aspect of language development in early childhood, playing a crucial role in communication and concept comprehension. This study aims to examine the effectiveness of the digital literacy game Wordwall in improving vocabulary skills in early childhood. The research was conducted using an experimental method with a quasi-experimental design involving 20 children. The analysis showed that the post-test average score of the experimental group (60) was higher than that of the control group (46). The t-test with pooled variance yielded tcalculated=6.35, greater than ttable=2.101, indicating a statistically significant improvement. Digital literacy games using the Wordwall application have proven effective in creating interactive and engaging learning, enhancing learning motivation, and strengthening early childhood vocabulary mastery.